Lead-acid battery

By using lead alloys with controlled CA and SN content and a specific organic shrinkage agent in the electrode materials, the low-temperature HR discharge performance of lead-acid batteries is maintained by reducing elution and corrosion, ensuring better discharge capacity and charging acceptance.

JP7622635B2Active Publication Date: 2025-01-28GS YUASA CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021548958
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-09-27
Filing Date
2020-09-24
Publication Date
2025-01-28
Estimated Expiration
2040-09-24

AI Technical Summary

Technical Problem

The low-temperature high-rate (HR) discharge performance of lead-acid batteries deteriorates due to the elution of organic shrinkage agents from the negative electrode material and corrosion of the positive electrode collector during charging and discharging cycles, especially in high-temperature environments, reducing the effective reaction area and overall performance.

Method used

Incorporating a positive electrode collector made of lead alloys with controlled CA and SN content, and using a first organic shrinkage agent composed of single-ring aromatic compounds and bisphenol S compounds in the negative electrode material to enhance adsorption and reduce elution, thereby maintaining the effective reaction area and suppressing corrosion.

Benefits of technology

The solution effectively suppresses the decrease in low-temperature HR discharge performance after repeated charging and discharging cycles, maintaining a higher discharge capacity and improved charging acceptance by reducing organic agent elution and collector corrosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007622635000002
    Figure 0007622635000002
  • Figure 0007622635000001
    Figure 0007622635000001
Patent Text Reader

Abstract

In the present invention, a lead acid storage battery comprises a positive electrode plate, a negative electrode plate, and an electrolytic solution. The positive electrode plate includes a positive electrode collector and a positive electrode material. The negative electrode plate includes a negative electrode collector and a negative electrode material. The positive electrode collector contains a lead alloy containing Ca and Sn. The Ca content of the positive electrode collector is 0.2 mass% or below and the Sn content thereof is 0.5 mass% or above. The negative electrode material contains a first organic shrink-proofing agent (excluding lignin compounds) including at least one unit selected from the group consisting of monocyclic aromatic compound units and bisphenol S compound units.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a lead-acid battery. [Background technology]

[0002] Lead-acid batteries are used in various applications, including automotive and industrial applications. Lead-acid batteries include a negative electrode plate, a positive electrode plate, and an electrolyte. The negative electrode plate includes a current collector and a negative electrode material. An organic shrinkage inhibitor is added to the negative electrode material. As the organic shrinkage inhibitor, in addition to naturally occurring organic shrinkage inhibitors such as sodium lignin sulfonate, synthetic organic shrinkage inhibitors are also used. As the synthetic organic shrinkage inhibitor, for example, a bisphenol condensate can be mentioned.

[0003] Patent Document 1 describes a lead-acid battery including a positive electrode, a negative electrode, and an electrolyte, in which the negative electrode has a negative electrode material and a negative electrode current collector, the negative electrode material contains a bisphenol resin and a negative electrode active material, the negative electrode current collector has a lug portion, and the lug portion is formed with a surface layer of Sn or a Sn alloy.

[0004] Patent Document 2 describes a flooded lead-acid battery comprising a negative electrode active material mainly composed of sponge lead, a positive electrode active material mainly composed of lead dioxide, and a freely flowing electrolyte solution containing sulfuric acid, wherein the negative electrode active material contains carbon, at least one material selected from the group consisting of cellulose ether, polycarboxylic acid, and salts thereof, and a water-soluble polymer made of a bisphenol-based condensate having a sulfonic acid group, and the positive electrode active material contains antimony.

[0005] Patent Document 3 describes a flooded lead-acid battery comprising a negative electrode active material mainly composed of sponge lead, a positive electrode active material mainly composed of lead dioxide, and a freely flowing electrolyte containing sulfuric acid, wherein the negative electrode active material contains, per 100 mass% of the sponge lead in a chemically-formed state, 0.5 mass% to 2.5 mass% of carbon black, a water-soluble polymer made of a bisphenol-based condensate having a sulfonic acid group as a substituent, and at least one polycarboxylic acid compound selected from the group consisting of polyacrylic acid, polymethacrylic acid, and polymaleic acid and their salts, and the electrolyte has a carbon black concentration of 3 massppm or less in a chemically-formed state.

[0006] Patent Document 4 describes a valve-regulated lead-acid battery including a positive electrode plate, a negative electrode plate, and an electrolyte, in which the negative electrode plate has a negative electrode current collector and a negative electrode material, and the density of the negative electrode material is 2.6 g / cm 3 and a valve regulated lead-acid battery in which the negative electrode material contains an organic shrinkage preventer and the content of sulfur element in the organic shrinkage preventer is greater than 600 μmol / g. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2017-79166 A [Patent Document 2] International Publication No. 2013 / 150754 [Patent Document 3] JP 2013-161606 A [Patent Document 4] JP 2018-18742 A Summary of the Invention [Problem to be solved by the invention]

[0008] When the charge-discharge cycle is performed, the organic shrinkage inhibitor gradually elutes from the negative electrode material, reducing the specific surface area of ​​the negative electrode material and causing a decrease in low-temperature high-rate (HR) discharge performance. In addition, when the corrosion of the positive electrode current collector progresses due to the charge-discharge cycle and the reaction area of ​​the positive electrode plate decreases, the reaction area of ​​the opposing negative electrode plate also decreases, causing a decrease in low-temperature HR discharge performance. Such a decrease in low-temperature HR discharge performance is particularly noticeable after charge-discharge cycles in a high-temperature environment. [Means for solving the problem]

[0009] One aspect of the present invention is a battery comprising a positive electrode plate, a negative electrode plate, and an electrolyte solution, The positive electrode plate includes a positive electrode current collector and a positive electrode material, The negative electrode plate includes a negative electrode current collector and a negative electrode material, The positive electrode current collector includes a lead alloy containing Ca and Sn, The Ca content in the positive electrode current collector is 0.2 mass% or less, and the Sn content is 0.5 mass% or more, The negative electrode material relates to a lead-acid battery, and includes a first organic shrinkage expander (excluding a lignin compound) that includes at least one selected from the group consisting of a monocyclic aromatic compound unit and a bisphenol S compound unit. Effect of the Invention

[0010] This can suppress the deterioration of the low-temperature HR discharge performance of a lead-acid battery after charge-discharge cycles. [Brief description of the drawings]

[0011] [Figure 1] 1 is a partially cutaway exploded perspective view showing the appearance and internal structure of a lead-acid battery according to one aspect of the present invention. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] A lead-acid battery according to one aspect of the present invention includes a positive plate, a negative plate, and an electrolyte. The positive plate includes a positive current collector and a positive electrode material. The negative plate includes a negative current collector and a negative electrode material. The positive current collector includes a lead alloy containing Ca and Sn. The Ca content in the positive current collector is 0.2 mass% or less, and the Sn content is 0.5 mass% or more. The negative electrode material includes a first organic shrink-proofing agent (excluding a lignin compound) including at least one selected from the group consisting of a monocyclic aromatic compound unit and a bisphenol S compound unit.

[0013] The first organic shrinkage inhibitor is an organic shrinkage inhibitor other than a lignin compound, which has at least one selected from the group consisting of a monocyclic aromatic compound unit and a bisphenol S compound unit. The first organic shrinkage inhibitor is a synthetic organic shrinkage inhibitor. The synthetic organic shrinkage inhibitor used in lead-acid batteries is usually an organic condensate (hereinafter simply referred to as a condensate). A condensate is a synthetic product that can be obtained by utilizing a condensation reaction. Since lignin compounds are natural materials, they are excluded from the synthetic condensates (synthetic organic shrinkage inhibitors).

[0014] In general, when a lead-acid battery is repeatedly charged and discharged, the organic shrinkage inhibitor gradually elutes from the negative electrode material, reducing the specific surface area of ​​the negative electrode material and causing a decrease in low-temperature HR discharge performance. Furthermore, when a lead-acid battery is repeatedly charged and discharged, the corrosion of the positive electrode current collector progresses and the reaction area of ​​the positive plate decreases. When the reaction area of ​​the positive plate decreases, the reaction area of ​​the opposing negative plate also decreases, which also causes a decrease in low-temperature HR discharge performance. In particular, in charge-discharge cycles in a high-temperature environment, such a decrease in low-temperature HR discharge performance becomes noticeable.

[0015] Unlike the naturally occurring lignin compound and the condensate of the bisphenol A compound, the first organic shrinkage inhibitor is likely to form a part having a planar structure in the molecule. Therefore, the first organic shrinkage inhibitor has high adsorption to lead and lead sulfate contained in the negative electrode material. Therefore, even if charging and discharging are performed in a high temperature environment, the elution of the organic shrinkage inhibitor is suppressed, and the decrease in the specific surface area of ​​the negative electrode material is suppressed. In contrast, the lignin compound has a complex three-dimensional mesh structure. In addition, the condensate of the bisphenol A compound has a structure in which the methylene group connecting the two benzene rings of the bisphenol A compound protrudes from the surface of the benzene ring. Therefore, the lignin compound and the condensate of the bisphenol A compound have inferior adsorption to the lead and lead sulfate contained in the negative electrode material compared to the first organic shrinkage inhibitor.

[0016] In addition, when the first organic shrinkage inhibitor is used, the overvoltage of the negative plate during charging is reduced compared to the case of the condensate of the lignin compound and the bisphenol A compound, and this results in an increase in the overvoltage of the positive plate during constant voltage charging. When the overvoltage of the positive plate increases, the corrosion of the positive electrode current collector is more likely to progress, and the effective reaction area of ​​the positive plate decreases. When the effective reaction area of ​​the positive plate decreases, the effective reaction area of ​​the opposing negative plate also decreases. Therefore, it is difficult to fully exert the effect of the first organic shrinkage inhibitor in suppressing the decrease in the specific surface area of ​​the negative electrode material.

[0017] In a lead-acid battery according to one aspect of the present invention, the Ca and Sn contents in the positive electrode collector are controlled, and a first organic shrinkage inhibitor is used in the negative electrode material. By controlling the Ca and Sn contents in the positive electrode collector, corrosion of the positive electrode collector is suppressed, and the reduction in the effective reaction area of ​​the positive and negative electrode plates is suppressed. Therefore, the first organic shrinkage inhibitor is able to fully exert the effect of suppressing the reduction in the specific surface area of ​​the negative electrode material. As a result, the reduction in low-temperature HR discharge performance after charge-discharge cycles can be effectively suppressed.

[0018] In this specification, the low-temperature HR discharge performance of a lead-acid battery after charge / discharge cycles refers to the low-temperature HR discharge performance after a fully charged lead-acid battery is repeatedly charged and discharged under a specified condition. More specifically, a fully charged lead-acid battery is placed in a water tank at 60°C ± 0.5°C, discharged at 25A for 4 minutes, and then charged at 2.47V / cell for 10 minutes with the upper limit of the current set to 25A. This discharge and charge cycle is counted as one cycle, and the low-temperature HR discharge performance is measured after 960 cycles.

[0019] In this specification, the fully charged state of a flooded lead-acid battery is defined by the definition of JIS D 5301:2006. More specifically, the fully charged state is defined as a state in which a lead-acid battery is charged in a water tank at 25°C ± 2°C with a current (A) 0.2 times the value listed as the rated capacity (Ah) until the terminal voltage during charging or the electrolyte density converted to a temperature of 20°C shows a constant value with three significant digits three times in a row. In addition, in the case of a valve-regulated lead-acid battery, the fully charged state is defined as a state in which a lead-acid battery is charged at a constant current and constant voltage of 2.23 V / cell in an air tank at 25°C ± 2°C with a current (A) 0.2 times the value listed as the rated capacity (Ah), and charging is terminated when the charging current (A) during constant voltage charging becomes 0.005 times the value listed as the rated capacity. The value listed as the rated capacity is expressed in Ah. The unit of current set based on the value stated as the rated capacity is A.

[0020] A fully charged lead-acid battery means a lead-acid battery that has already been formed and is fully charged. The lead-acid battery may be fully charged immediately after formation, or after some time has passed since formation. For example, a lead-acid battery that is in use (preferably in the early stages of use) after formation may be fully charged. A battery in the early stages of use means a battery that has not been in use for very long and has hardly deteriorated.

[0021] In the present specification, the lignin compound includes lignin and lignin derivatives. The lignin derivative includes a compound having a lignin-like three-dimensional structure. The lignin derivative includes at least one selected from the group consisting of modified lignin, lignin sulfonic acid, modified lignin sulfonic acid, and salts thereof (alkali metal salts (such as sodium salts), magnesium salts, calcium salts, etc.).

[0022] The lead acid battery may be either a valve regulated (sealed) lead acid battery or a flooded (vented) lead acid battery.

[0023] Hereinafter, the lead-acid battery and the negative electrode plate according to the embodiment of the present invention will be described in detail with respect to each of their main components, but the present invention is not limited to the following embodiment.

[0024] [Lead acid battery] (Negative plate) The negative electrode plate includes a negative current collector and a negative electrode material. The negative electrode material is the portion of the negative electrode plate excluding the negative current collector. Note that a member such as a mat or pasting paper may be attached to the negative electrode plate. Such a member (attaching member) is used integrally with the negative electrode plate and is therefore included in the negative electrode plate. Also, when the negative electrode plate includes an attaching member, the negative electrode material is the portion of the negative electrode plate excluding the negative current collector and the attaching member. However, when an attaching member (such as a mat or pasting paper) is attached to the separator, the thickness of the attaching member is included in the thickness of the separator.

[0025] The negative electrode current collector may be formed by casting lead (Pb) or a lead alloy, or may be formed by processing a lead sheet or a lead alloy sheet. Examples of the processing method include expanding and punching. It is preferable to use a lattice-shaped current collector as the negative electrode current collector because it is easy to support the negative electrode material.

[0026] The lead alloy used for the negative electrode current collector may be any of Pb-Sb alloy, Pb-Ca alloy, and Pb-Ca-Sn alloy. These lead or lead alloys may further contain at least one selected from the group consisting of Ba, Ag, Al, Bi, As, Se, Cu, etc. as an additive element. The negative electrode current collector may have a surface layer. The surface layer and the inner layer of the negative electrode current collector may have different compositions. The surface layer may be formed on a part of the negative electrode current collector. The surface layer may be formed on the ear of the negative electrode current collector. The surface layer of the ear may contain Sn or an Sn alloy.

[0027] The negative electrode material includes a first organic shrinkage inhibitor. The negative electrode material usually further includes a negative electrode active material (lead or lead sulfate) that develops capacity by an oxidation-reduction reaction. The negative electrode material may include at least one selected from the group consisting of another organic shrinkage inhibitor (hereinafter sometimes referred to as a second organic shrinkage inhibitor), a carbonaceous material, and another additive. Examples of additives include barium sulfate and fibers (such as resin fibers), but are not limited to these. The negative electrode active material in a charged state is sponge-like lead, and the unformed negative plate is usually made using lead powder.

[0028] (Organic shrink-proofing agent) The negative electrode material includes an organic shrinkage inhibitor. The organic shrinkage inhibitor is an organic compound among compounds that have the function of suppressing the shrinkage of lead, which is the negative electrode active material, when the lead-acid battery is repeatedly charged and discharged. As already described, the negative electrode material includes a first organic shrinkage inhibitor as an essential component among the organic shrinkage inhibitors, and may further include a second organic shrinkage inhibitor as necessary. The second organic shrinkage inhibitor is an organic shrinkage inhibitor other than the first organic shrinkage inhibitor. The organic shrinkage inhibitor may be, for example, an organic shrinkage inhibitor synthesized by a known method, or a commercially available product.

[0029] Examples of the organic shrink-proofing agents include organic condensates (hereinafter, simply referred to as condensates). Condensates are synthetic products, and are generally also referred to as synthetic organic shrink-proofing agents. The condensates may contain units of aromatic compounds (hereinafter, also referred to as aromatic compound units). The aromatic compound units refer to units derived from aromatic compounds incorporated in the condensates. That is, the aromatic compound units are residues of aromatic compounds. The condensates may contain one type of aromatic compound unit, or two or more types. The organic shrink-proofing agent also includes the above-mentioned lignin compound.

[0030] The condensate may be, for example, a condensate of an aromatic compound with an aldehyde compound. Such a condensate may be synthesized by reacting an aromatic compound with an aldehyde compound. Here, a condensate containing a sulfur element may be obtained by carrying out the reaction of an aromatic compound with an aldehyde compound in the presence of a sulfite, or by using an aromatic compound containing a sulfur element (e.g., bisphenol S) as an aromatic compound. For example, the sulfur element content in the condensate may be adjusted by adjusting at least one of the amount of sulfite and the amount of the aromatic compound containing a sulfur element. This method may be followed when using other raw materials. The aromatic compound to be condensed to obtain the condensate may be one type or two or more types. The aldehyde compound may be an aldehyde (e.g., formaldehyde), or may be a condensate (or polymer) of an aldehyde. Examples of the aldehyde condensate (or polymer) include paraformaldehyde, trioxane, and tetraoxymethylene. The aldehyde compound may be used alone or in combination of two or more types. From the viewpoint of high reactivity with aromatic compounds, formaldehyde is preferred.

[0031] The aromatic compound may have a sulfur-containing group. That is, the condensate may be an organic polymer containing a plurality of aromatic rings and a sulfur element as a sulfur-containing group in the molecule. The sulfur-containing group may be directly bonded to the aromatic ring of the aromatic compound, or may be bonded to the aromatic ring as an alkyl chain having a sulfur-containing group, for example. Among the sulfur-containing groups, a sulfonic acid group or a sulfonyl group, which is a stable form, is preferred. The sulfonic acid group may exist in an acid form or in a salt form such as a Na salt.

[0032] The sulfur-containing group is a functional group with a strong negative polarity. In an electrolyte, such functional groups form stable bonds with water molecules, hydrogen ions, and hydrogen sulfate ions, so that the functional groups tend to be unevenly distributed on the surface of the condensate. Since such functional groups unevenly distributed on the surface have a negative charge, electrostatic repulsion occurs between the associations of the condensate. This limits the association or aggregation of colloidal particles of the condensate, and the colloidal particle size tends to be small. As a result, it is considered that the pore size of the negative electrode material is small and the resistivity of the negative electrode material is likely to decrease. Therefore, when a condensate having a sulfur-containing group is used, a higher shrinkage prevention effect can be secured, and excellent low-temperature HR discharge performance and charge acceptance can be easily obtained.

[0033] Examples of the aromatic rings that aromatic compounds have include benzene rings and naphthalene rings. When an aromatic compound has multiple aromatic rings, the multiple aromatic rings may be linked by direct bonds or linking groups (e.g., alkylene groups (including alkylidene groups), sulfone groups) and the like. Examples of such structures include bisarene structures (biphenyl, bisphenylalkane, bisphenylsulfone, etc.).

[0034] Examples of aromatic compounds include compounds having the above aromatic ring and a functional group (such as a hydroxy group or an amino group). The functional group may be directly bonded to the aromatic ring, or may be bonded as an alkyl chain having a functional group. The hydroxy group also includes a salt of the hydroxy group (-OMe). The amino group also includes a salt of the amino group (a salt with an anion). Examples of Me include alkali metals (Li, K, Na, etc.) and metals of Group 2 of the periodic table (Ca, Mg, etc.). The aromatic compound may have a sulfur-containing group and a substituent other than the above functional group (such as an alkyl group or an alkoxy group) on the aromatic ring.

[0035] The aromatic compound that is the source of the aromatic compound unit may be at least one selected from the group consisting of bisarene compounds and monocyclic aromatic compounds.

[0036] Examples of the bisarene compound include bisarene compounds having a hydroxy group (such as bisphenol compounds and hydroxybiphenyl compounds), and bisarene compounds having an amino group (such as bisarylalkane compounds having an amino group, bisarylsulfone compounds having an amino group, and biphenyl compounds having an amino group). Among these, bisarene compounds having a hydroxy group (particularly, bisphenol compounds) are preferred.

[0037] The bisphenol compound is preferably bisphenol A, bisphenol S, bisphenol F, or the like. For example, the bisphenol compound may contain at least one selected from the group consisting of bisphenol A and bisphenol S. By using bisphenol A or bisphenol S, a higher shrinkage prevention effect is easily obtained for the negative electrode material.

[0038] The bisphenol compound may have a bisphenol skeleton, and the bisphenol skeleton may have a substituent. That is, bisphenol A may have a bisphenol A skeleton, and the skeleton may have a substituent. Bisphenol S may have a bisphenol S skeleton, and the skeleton may have a substituent.

[0039] Preferred monocyclic aromatic compounds include hydroxymonoarene compounds, monocyclic aromatic compounds having an amino group (aminomonoarene compounds), etc. Among these, hydroxymonoarene compounds are preferred.

[0040] Examples of the hydroxymonoarene compound include a hydroxynaphthalene compound and a phenol compound. For example, it is preferable to use a phenolsulfonic acid compound (phenolsulfonic acid or a substituted compound thereof) which is a phenol compound. As mentioned above, the phenolic hydroxy group also includes a salt of the phenolic hydroxy group (-OMe).

[0041] Examples of the aminomonoarene compounds include aminonaphthalene compounds and aniline compounds (such as aminobenzenesulfonic acid and alkylaminobenzenesulfonic acid).

[0042] The sulfur element content of the organic shrink-proofing agent other than the lignin compound may be, for example, 2000 μmol / g or more, or 3000 μmol / g or more. When an organic shrink-proofing agent having such a sulfur element content is used, the colloidal particle size of the organic shrink-proofing agent tends to become small, and high low-temperature HR discharge performance after cycling is easily ensured.

[0043] The sulfur element content in the organic shrink-preventer being X μmol / g means that the content of sulfur element contained in 1 g of the organic shrink-preventer is X μmol.

[0044] The upper limit of the sulfur element content of the organic shrink inhibitor other than the lignin compound is not particularly limited, but may be, for example, 9000 μmol / g or less, 8000 μmol / g or less, or 7000 μmol / g or less.

[0045] The organic shrink-proofing agent other than the lignin compound also includes an organic shrink-proofing agent having an elemental sulfur content of less than 2000 μmol / g. The elemental sulfur content of such an organic shrink-proofing agent may be 300 μmol / g or more.

[0046] The sulfur element content of the organic shrink inhibitor other than the lignin compound may be, for example, 2000 μmol / g or more (or 3000 μmol / g or more) and 9000 μmol / g or less, 2000 μmol / g or more (or 3000 μmol / g or more) and 8000 μmol / g or less, 2000 μmol / g or more (or 3000 μmol / g or more) and 7000 μmol / g or less, 300 μmol / g or more and 9000 μmol / g or less (or 8000 μmol / g or less), or 300 μmol / g or more and 7000 μmol / g or less (or less than 2000 μmol / g).

[0047] The weight average molecular weight (Mw) of the organic shrink-proofing agent other than the lignin compound is, for example, preferably not less than 7000. The Mw of the organic shrink-proofing agent is, for example, not more than 100,000, and may be not more than 20,000.

[0048] The sulfur element content of the lignin compound is, for example, less than 2000 μmol / g, and may be 1000 μmol / g or less, or 800 μmol / g or less. The lower limit of the sulfur element content of the lignin compound is not particularly limited, but is, for example, 400 μmol / g or more.

[0049] The Mw of the lignin compound is, for example, less than 7000. The Mw of the lignin compound is, for example, 3000 or more.

[0050] In the present specification, the Mw of the organic shrink-preventing agent is determined by gel permeation chromatography (GPC). The standard substance used in determining the Mw is sodium polystyrene sulfonate. Mw is measured using the following apparatus under the following conditions. GPC equipment: Build-up GPC system SD-8022 / DP-8020 / AS-8020 / CO-8020 / UV-8020 (Tosoh Corporation) Column: TSKgel G4000SWXL, G2000SWXL (7.8 mm I.D. x 30 cm) (Tosoh Corporation) Detector: UV detector, λ=210nm Eluent: A mixture of 1 mol / L NaCl aqueous solution: acetonitrile (volume ratio = 7:3) Flow rate: 1mL / min. Concentration: 10mg / mL Injection volume: 10μL Standard substance: Sodium polystyrene sulfonate (Mw=275,000, 35,000, 12,500, 7,500, 5,200, 1,680)

[0051] Among the organic shrinkage inhibitors, the first organic shrinkage inhibitor is an organic shrinkage inhibitor (e.g., condensation product) containing at least one selected from the group consisting of monocyclic aromatic compound units and bisphenol S compound units among the above aromatic compound units. Among the monocyclic aromatic compounds, monocyclic compounds (e.g., hydroxymonoarene compounds) having a hydroxy group (particularly, a phenolic hydroxy group) are preferred. In the condensation product of a monocyclic aromatic compound having a phenolic hydroxy group with an aldehyde compound, the condensation is mainly at least one of the ortho and para positions (particularly the ortho position) with respect to the phenolic hydroxy group. On the other hand, in the condensation product of a monocyclic compound having an amino group with an aldehyde compound, the condensation is performed via the amino group. Therefore, when a monocyclic compound having a phenolic hydroxy group is used, the aromatic rings in the organic shrinkage inhibitor molecule are less twisted than when a monocyclic compound having an amino group is used, and it is easier to take a planar structure, which is thought to make it easier to act on lead and lead sulfate. Furthermore, the phenolic hydroxy group makes it easier for the first organic shrink-preventing agent to be negatively charged than an amino group or the like, and therefore makes it easier to obtain high adsorption to lead.

[0052] Among the units of monocyclic aromatic compounds, it is preferable to use a first organic shrinkage inhibitor containing a unit of a phenolsulfonic acid compound. Such a first organic shrinkage inhibitor has a phenolic hydroxy group and a sulfonic acid group. Both the phenolic hydroxy group and the sulfonic acid group have strong negative polarity and high affinity with metals. In addition, the condensate is likely to have a planar structure due to phenolsulfonic acid. Therefore, the condensate containing the unit of a phenolsulfonic acid compound has a higher adsorption property to lead and lead sulfate. Therefore, when such a condensate is used, the elution of the condensate from the negative electrode material can be more effectively suppressed.

[0053] The first organic shrink-proofing agent may contain a unit of a monocyclic aromatic compound (hereinafter, sometimes referred to as the first unit) and a unit of another aromatic compound (hereinafter, sometimes referred to as the second unit). An example of the second unit is a unit of a bisarene compound. An example of the second unit is at least one selected from the group consisting of a unit of a bisphenol S compound and a unit of a bisphenol A compound. In an organic shrink-proofing agent containing a second unit, the aromatic ring generally tends to interact with each other between π electrons and become rigid. However, in the first organic shrink-proofing agent, the first unit inhibits the interaction between π electrons of the second unit, so that the flexibility of the molecule can be increased. In addition, the organic shrink-proofing agent usually contains many functional groups having negative polarity. It is considered that the flexibility of the molecule is increased in the first organic shrink-proofing agent, so that the functional groups having negative polarity contained in the first organic shrink-proofing agent tend to be unevenly distributed on the molecular surface. As a result, the elution of the first organic shrink-proofing agent from the negative electrode material is further suppressed, so that the deterioration of the low-temperature HR discharge performance after the charge-discharge cycle can be further suppressed.

[0054] When the first organic shrinkage inhibitor contains the first unit and the second unit, the molar ratio of the first unit to the total amount of these units is, for example, 10 mol% or more, and may be 20 mol% or more, 40 mol% or more, or 50 mol% or more. When the molar ratio is in such a range, the first shrinkage inhibitor is more likely to have a planar structure. Therefore, the elution from the negative electrode material is reduced, and high low-temperature HR discharge performance after charge-discharge cycles is obtained. The molar ratio of the first unit is, for example, 90 mol% or less, and may be 80 mol% or less. When the molar ratio of the first unit is in such a range, the condensate is more likely to be negatively charged. Therefore, the elution from the negative electrode material is reduced, and high low-temperature HR discharge performance after charge-discharge cycles can be ensured.

[0055] The molar ratio of the first unit may be 10 mol% or more (or 20 mol% or more) and 90 mol% or less, 10 mol% or more (or 20 mol% or more) and 80 mol% or less, 40 mol% or more (or 50 mol% or more) and 90 mol% or less, or 40 mol% or more (or 50 mol% or more) and 80 mol% or less.

[0056] The second unit is preferably at least a bisphenol S compound unit. The first organic shrinkage inhibitor may contain a bisphenol S compound unit and a bisphenol A compound unit as the second unit. The bisphenol S skeleton has a structure in which two benzene rings are linked by a sulfonyl group. The bisphenol A skeleton has a structure in which two benzene rings are linked by a dimethylene group. The sulfonyl group protrudes less from the benzene ring plane than the dimethylene group. Therefore, the bisphenol S compound unit makes it easier for the first organic shrinkage inhibitor to have a planar structure compared to the bisphenol A compound unit. In addition, due to the presence of the sulfonyl group, the bisphenol S compound unit makes it easier for the first organic shrinkage inhibitor to be negatively charged compared to the bisphenol A compound unit. Therefore, when a first organic shrinkage inhibitor having at least a bisphenol S compound unit is used as the second unit, the adsorption of the first organic shrinkage inhibitor to lead is further increased.

[0057] Also, an organic shrink-proofing agent (condensation product) containing at least a bisphenol S compound unit may be used as the first organic shrink-proofing agent. As described above, the bisphenol S compound has a sulfonyl group, which makes the first organic shrink-proofing agent easily negatively charged. Therefore, by using a first organic shrink-proofing agent having at least a bisphenol S compound unit, the adsorption of the first organic shrink-proofing agent to lead can be further increased. Also, as the first organic shrink-proofing agent, one containing a bisphenol S compound unit and a bisphenol A compound unit (condensation product) may be used. The first organic shrink-proofing agent having these units has a smaller colloid particle diameter than a condensation product of bisphenol S alone, and a higher shrink-proofing effect can be obtained.

[0058] When the first organic shrinkage inhibitor contains a bisphenol S compound unit and a bisphenol A compound unit, the molar ratio of the bisphenol S compound unit to the total amount of these units is, for example, 10 mol or more, and may be 20 mol% or more. From the viewpoint of easily ensuring high adsorption by the bisphenol S compound, the molar ratio of the bisphenol S compound unit is preferably 40 mol% or more, and may be 50 mol% or more. From the viewpoint of more easily generating fine colloidal particles, the molar ratio of the bisphenol S compound unit is, for example, 90 mol% or less, and may be 80 mol% or less.

[0059] When the first organic shrinkage agent contains units of a bisphenol S compound and units of a bisphenol A compound, the molar ratio of the units of the bisphenol S compound to the total amount of these units may be 10 mol% or more (or 20 mol% or more) and 90 mol% or less, 40 mol% or more (or 50 mol% or more) and 90 mol% or less, 10 mol% or more (or 20 mol% or more) and 80 mol% or less, or 40 mol% or more (or 50 mol% or more) and 80 mol% or less.

[0060] The sulfur element content and Mw of the first organic shrink-proofing agent can each be selected from the above ranges.

[0061] The first organic shrink-proofing agent may be used alone or in combination of two or more kinds.

[0062] Among the above organic shrink-proofing agents, examples of the second organic shrink-proofing agent include a condensation product of a lignin compound and a bisphenol A compound with an aldehyde compound. The second organic shrink-proofing agent may be used alone or in combination of two or more kinds.

[0063] The sulfur element content of the lignin compound is, for example, less than 2000 μmol / g, and may be 1000 μmol / g or less, or 800 μmol / g or less. The lower limit of the sulfur element content of the lignin compound is not particularly limited, but is, for example, 400 μmol / g or more.

[0064] The Mw of the lignin compound is, for example, less than 7000. The Mw of the lignin compound is, for example, 3000 or more.

[0065] When the first organic shrinkage inhibitor and the second organic shrinkage inhibitor are used in combination, the mass ratio of the first organic shrinkage inhibitor and the second organic shrinkage inhibitor can be selected arbitrarily. Even when the second organic shrinkage inhibitor is used in combination, the effect of suppressing the decrease in low-temperature HR discharge performance after charge-discharge cycles can be obtained according to the mass ratio of the first organic shrinkage inhibitor. From the viewpoint of ensuring higher low-temperature HR discharge performance after charge-discharge cycles, the ratio of the first organic shrinkage inhibitor to the entire organic shrinkage inhibitor (i.e., the total amount of the first organic shrinkage inhibitor and the second organic shrinkage inhibitor) is preferably 50 mass% or more, may be 80 mass% or more, may be 90 mass% or more, or may be 95 mass% or more.

[0066] The content of the organic shrink-proofing agent in the negative electrode material is, for example, 0.01% by mass or more, and may be 0.05% by mass or more.The content of the organic shrink-proofing agent is, for example, 1.0% by mass or less, and may be 0.5% by mass or less.

[0067] The content of the organic shrinkage inhibitor in the negative electrode material may be 0.01% by mass or more and 1.0% by mass or less, 0.05% by mass or more and 1.0% by mass or less, 0.01% by mass or more and 0.5% by mass or less, or 0.05% by mass or more and 0.5% by mass or less.

[0068] (Barium Sulfate) The negative electrode material may contain barium sulfate. When the first organic shrinkage inhibitor is used, the surface of the lead is covered with the first organic shrinkage inhibitor, which tends to reduce the charge acceptance. By using barium sulfate as the negative electrode material, the decrease in charge acceptance can be reduced.

[0069] The content of barium sulfate in the negative electrode material is, for example, 0.05% by mass or more, and may be 0.1% by mass or more or 0.5% by mass or more. From the viewpoint of ensuring higher low-temperature HR discharge performance after charge-discharge cycles, the content of barium sulfate is preferably 0.6% by mass or more, and more preferably 0.8% by mass or more. When the content of barium sulfate is in such a range, the barium sulfate acts as a crystal nucleus during discharge, and a large number of fine and easily reactive lead sulfates are generated. As a result, the discharge reaction becomes more uniform over the entire negative electrode plate, suppressing the contraction of the negative electrode material and maintaining a large specific surface area. In addition, since a large amount of the first organic shrinkage inhibitor remains in the negative electrode material after the charge-discharge cycles, the surface of the negative electrode material is stabilized by the first organic shrinkage inhibitor, and a large specific surface area is maintained. It is believed that these can ensure higher low-temperature HR discharge performance after the charge-discharge cycles.

[0070] Furthermore, when the first organic shrinkage inhibitor contains the first unit, the crystals of lead sulfate generated during discharge tend to be larger than those of a lignin compound or a condensate of bisphenol A, which tends to slightly decrease the charge acceptance. Therefore, when using a first organic shrinkage inhibitor containing the first unit, from the viewpoint of ensuring higher charge acceptance by making the lead sulfate finer, the content of barium sulfate is preferably 0.6% by mass or more, and more preferably 0.8% by mass or more.

[0071] The content of barium sulfate in the negative electrode material is 5% by mass or less, and may be 3% by mass or less.

[0072] The content of barium sulfate in the negative electrode material may be 0.05% by mass or more (or 0.1% by mass or more) and 5% by mass or less, 0.05% by mass or more (or 0.1% by mass or more) and 3% by mass or less, 0.5% by mass or more (or 0.6% by mass or more) and 5% by mass or less, 0.5% by mass or more (or 0.6% by mass or more) and 3% by mass or less, or 0.8% by mass or more and 5% by mass or less (or 3% by mass or less).

[0073] (carbonaceous material) The negative electrode material may include a carbonaceous material. Examples of the carbonaceous material include carbon black, graphite, hard carbon, and soft carbon. Examples of carbon black include acetylene black, furnace black, and lamp black. Furnace black also includes Ketjen Black (trade name). The graphite may be any carbonaceous material that includes a graphite-type crystal structure, and may be either artificial graphite or natural graphite. The carbonaceous material may be used alone or in combination of two or more.

[0074] The content of the carbonaceous material in the negative electrode material is, for example, preferably 0.05% by mass or more, and may be 0.10% by mass or more, and the content of the carbonaceous material is, for example, 5% by mass or less, and may be 3% by mass or less.

[0075] The content of the carbonaceous material in the negative electrode material may be, for example, 0.05% by mass to 5% by mass, 0.05% by mass to 3% by mass, 0.10% by mass to 5% by mass, or 0.10% by mass to 3% by mass.

[0076] (Analysis of the components of negative electrode materials) The following describes a method for analyzing the negative electrode material or its components. The components of the negative electrode material are analyzed on the negative plate of a fully charged lead-acid battery. Prior to the analysis of the components, the lead-acid battery after chemical formation is fully charged and then disassembled to obtain the negative plate to be analyzed. The obtained negative plate is washed with water to remove sulfuric acid from the negative plate. The washing is continued until a pH test paper is pressed against the washed surface of the negative plate and it is confirmed that the color of the test paper does not change. However, the washing time should be within 2 hours. The washed negative plate is dried at 60±5°C for about 6 hours in a reduced pressure environment. After drying, if the negative plate contains an adhesive material, the adhesive material is removed from the negative plate by peeling. Next, the negative electrode material is separated from the negative plate to obtain a sample (hereinafter referred to as sample A). Sample A is crushed as necessary and subjected to analysis.

[0077] (1) Analysis of organic shrinkage inhibitors (1-1) Qualitative analysis of organic shrinkage inhibitors in negative electrode materials The crushed sample A is immersed in a 1 mol / L aqueous solution of sodium hydroxide (NaOH) to extract the organic shrink-preventing agent. If the extract contains multiple organic shrink-preventing agents, each organic shrink-preventing agent is then separated from the extract. For each of the isolated materials containing each organic shrink-preventing agent, insoluble components are removed by filtration, and the resulting solution is desalted, concentrated, and dried. Desalting is performed using a desalting column, or by passing the solution through an ion exchange membrane, or by placing the solution in a dialysis tube and immersing it in distilled water. This is dried to obtain a powder sample of the organic shrink-preventing agent (hereinafter referred to as sample B).

[0078] The type of organic shrink-preventing agent is identified by combining information obtained from the infrared spectrum measured using sample B of the organic shrink-preventing agent thus obtained, the ultraviolet-visible absorption spectrum measured with an ultraviolet-visible spectrometer after diluting sample B with distilled water or the like, or the NMR spectrum of a solution obtained by dissolving sample B in a specified solvent such as heavy water.

[0079] When the extract contains a plurality of organic shrink-preventing agents, they are separated as follows.

[0080] First, the extract is measured by at least one of infrared spectroscopy, NMR, and GC-MS to determine whether it contains multiple organic shrink-preventing agents. Next, the extract is subjected to GPC analysis to measure the molecular weight distribution. If the multiple organic shrink-preventing agents can be separated by molecular weight, the organic shrink-preventing agents are separated by column chromatography based on the difference in molecular weight.

[0081] The organic shrink-preventing agent has different solubilities if at least one of the type and amount of functional groups is different. When it is difficult to separate the organic shrink-preventing agent due to the difference in molecular weight, such a difference in solubility is utilized to separate one of the organic shrink-preventing agents by a precipitation separation method. For example, when two types of organic shrink-preventing agents are contained, one of the organic shrink-preventing agents is flocculated and separated by dropping an aqueous sulfuric acid solution into a mixture in which the above extract is dissolved in an aqueous NaOH solution to adjust the pH of the mixture. When separation by flocculation is difficult, the organic shrink-preventing agent is separated by ion exchange chromatography or affinity chromatography utilizing at least one of the difference in the type and amount of functional groups. The separated material is dissolved again in an aqueous NaOH solution, and the insoluble components are removed by filtration as described above. In addition, the remaining solution after separating one of the organic shrink-preventing agents is concentrated. The obtained concentrate contains the other organic shrink-preventing agent, and the insoluble components are removed by filtration from this concentrate as described above.

[0082] (1-2) Quantitative determination of organic shrinkage inhibitor content in negative electrode material As in the above (1-1), a solution is obtained by removing insoluble components from each of the separated products containing the organic shrinkage inhibitor by filtration. The ultraviolet-visible absorption spectrum of each of the obtained solutions is measured. The content of each organic shrinkage inhibitor in the negative electrode material is determined using the intensity of the peak characteristic of each organic shrinkage inhibitor and a calibration curve prepared in advance.

[0083] In addition, when a lead-acid battery with an unknown content of organic shrink-proofing agent is obtained and the content of the organic shrink-proofing agent is measured, the structural formula of the organic shrink-proofing agent cannot be precisely specified, so the same organic shrink-proofing agent cannot be used for the calibration curve. In this case, a calibration curve is created using the organic shrink-proofing agent extracted from the negative electrode of the battery and a separately available organic polymer that shows similar shapes in the ultraviolet-visible absorption spectrum, infrared spectroscopy spectrum, and NMR spectrum, and the content of the organic shrink-proofing agent is measured using the ultraviolet-visible absorption spectrum.

[0084] (1-3) Sulfur content in organic shrinkage inhibitors As in (1-1) above, after obtaining sample B of the organic shrink-proofing agent, the sulfur element in 0.1 g of the organic shrink-proofing agent is converted to sulfuric acid by the oxygen combustion flask method. At this time, sample B is burned in a flask containing an adsorption solution to obtain an eluate in which sulfate ions are dissolved in the adsorption solution. Next, the sulfur element content (C0) in 0.1 g of the organic shrink-proofing agent is obtained by titrating the eluate with barium perchlorate using thorin as an indicator. Next, C0 is multiplied by 10 to calculate the sulfur element content (μmol / g) in the organic shrink-proofing agent per 1 g.

[0085] (1-4) Calculation of the molar ratio of the constituent units of the organic shrinkage regulator First, the sample B of the organic shrink-preventing agent (the organic shrink-preventing agent to be measured) separated in the same manner as in (1-1) above is dissolved in a heavy water solution of sodium hydroxide (pH 10 to 13) to prepare a measurement sample. Using this measurement sample, 1 Measure H-NMR. 1 The units contained in the organic shrink-preventing agent are identified from the peaks in the H-NMR spectrum. 1 In the H-NMR spectrum, the ratio of the peak intensities of the peaks originating from each unit (first ratio) is determined.

[0086] Next, an organic shrink-preventing agent (reference organic shrink-preventing agent) containing the same unit as the identified structure and having a known mole fraction of each unit is synthesized. 1 1H-NMR spectrum is measured. 1 In the H-NMR spectrum, the ratio of the peak intensities of the peaks originating from each unit (second ratio) is determined.

[0087] A lead-acid battery is prepared using the reference organic shrinkage preventer and is fully charged. Sample A is taken from the negative electrode plate taken out of the fully charged lead-acid battery in the same manner as described above. Sample B is obtained from this sample A in the same manner as described in (1-1) above. The obtained sample B is dissolved in a heavy water solution of sodium hydroxide (pH 10 to 13) to prepare a measurement sample, and the measurement sample is used to perform the following: 1 1H-NMR is measured. 1In the H-NMR spectrum, the ratio of the peak intensities of the peaks originating from each unit (third ratio) is determined.

[0088] The third ratio may deviate from the second ratio, which indicates the actual molar fraction. Therefore, for correction, the relationship between the second ratio and the third ratio and the above-mentioned known molar fraction is obtained. This relationship indicates the relationship between the actual molar fraction of each unit and the peak intensity ratio of the peak of each unit of the organic shrink-proofing agent when it is taken out from the lead-acid battery. By applying the first ratio to this relationship, the molar fraction of each unit in the organic shrink-proofing agent to be measured can be obtained from the first ratio. Then, the ratio (mol%) of the molar fraction of each unit to the total of the molar fractions of each unit is calculated, and this is set as the molar fraction of each unit.

[0089] For example, when the first organic shrink-proofing agent is a condensation product of phenolsulfonic acid and bisphenol S with formaldehyde, 1 In the H-NMR spectrum, the peaks due to the bisphenol S unit (P bs ) in the range of 6.5 ppm to 6.6 ppm, and a peak derived from the phenolsulfonic acid unit (P ps ) are found in the range of more than 6.6 ppm and less than 7.0 ppm, respectively. 1 From H-NMR, peak P bs Peak intensity I bs and Peak P ps Peak intensity I ps The ratio (second ratio and third ratio) of the first organic shrink-preventing agent to the second and third ratios is then calculated. The relationship between the second and third ratios and the known molar fractions is then calculated. The relationship is then calculated based on the molar fraction of the first organic shrink-preventing agent, the molar fraction of which is unknown. 1 Peak P in H-NMR bs Peak intensity I bs and Peak P ps Peak intensity I ps By applying the ratio (first ratio) to the mole fraction m of the bisphenol S unit of the first organic shrinkage regulator, bs and the mole fraction of phenolsulfonic acid units mps Then, calculate the mole fraction m bs and mole fraction m ps The mole fraction m of phenolsulfonic acid units in the total of ps The ratio (mol %) of is calculated and is regarded as the molar ratio of the phenolsulfonic acid unit.

[0090] (2) Quantitative analysis of carbonaceous materials and barium sulfate 50 ml of 20% by mass nitric acid is added to 10 g of the crushed sample A, and the mixture is heated for about 20 minutes to dissolve the lead components as lead nitrate. Next, the solution containing lead nitrate is filtered to separate the carbonaceous material, barium sulfate, and other solids.

[0091] The obtained solid content is dispersed in water to obtain a dispersion, and then components other than the carbonaceous material and barium sulfate (e.g., reinforcing material) are removed from the dispersion using a sieve. Next, the dispersion is subjected to suction filtration using a membrane filter whose mass has been measured in advance, and the membrane filter together with the filtered sample is dried in a dryer at 110°C ± 5°C. The obtained sample is a mixed sample of the carbonaceous material and barium sulfate (hereinafter referred to as Sample C). The mass of the membrane filter is subtracted from the total mass of Sample C and the membrane filter after drying to obtain the mass of Sample C (M m ) is measured. After that, the dried sample C is placed in a crucible together with the membrane filter and incinerated at 700°C or higher. The remaining residue is barium oxide. The mass of barium oxide is converted to the mass of barium sulfate to obtain the mass of barium sulfate (M B ) is calculated. Mass M m From mass M B The mass of the carbonaceous material is calculated by subtracting the above.

[0092] (others) The negative electrode plate can be formed by applying or filling a negative electrode paste onto a negative electrode current collector, aging and drying to prepare an unformed negative electrode plate, and then chemically forming the unformed negative electrode plate. The negative electrode paste is prepared by adding water and sulfuric acid to lead powder, an organic shrinkage inhibitor, and various additives as necessary, and kneading them. When aging, it is preferable to age the unformed negative electrode plate at a temperature higher than room temperature and at a high humidity.

[0093] The formation can be carried out by immersing the plate group including the unformed negative plate in an electrolyte containing sulfuric acid in a lead-acid battery container and charging the plate group. However, the formation may be carried out before assembling the lead-acid battery or the plate group. The formation produces spongy lead.

[0094] (Positive plate) The positive electrode plate of a lead-acid battery usually includes a positive electrode current collector and a positive electrode material. The positive electrode material is held by the positive electrode current collector. The positive electrode plate of a lead-acid battery can be classified into a paste type, a clad type, and the like. Either the paste type or the clad type positive electrode plate may be used.

[0095] In a paste-type positive plate, the positive electrode material is the portion of the positive plate excluding the positive current collector. A member such as a mat or pasting paper may be attached to the positive plate. Such a member (attaching member) is used integrally with the positive plate, and is therefore included in the positive plate. In addition, when the positive plate includes an attaching member (mat, pasting paper, etc.), in a paste-type positive plate, the positive electrode material is the portion of the positive plate excluding the positive current collector and the attaching member.

[0096] The positive electrode current collector may be formed by casting a lead alloy, or may be formed by processing a lead sheet or a lead alloy sheet. Examples of the processing method include expanding and punching. It is preferable to use a lattice-shaped current collector as the positive electrode current collector because it is easy to support the positive electrode material.

[0097] The positive electrode current collector is made of a lead alloy containing Ca and Sn. By controlling the content of Ca and Sn in the positive electrode current collector, the corrosion of the positive electrode current collector due to the charge-discharge cycle is suppressed, and the effect of the first organic shrinkage inhibitor is effectively exhibited. Examples of the lead alloy used for the positive electrode current collector include Pb-Ca-Sn alloys.

[0098] The Ca content in the positive electrode current collector is 0.2 mass% or less. If the Ca content exceeds 0.2 mass%, a large amount of Ca-rich phase is precipitated at the grain boundaries of the Pb alloy, which causes significant intergranular corrosion, resulting in a significant decrease in low-temperature HR discharge performance after cycling. From the viewpoint of ensuring a higher corrosion inhibition effect of the positive electrode current collector, the Ca content is preferably 0.14 mass% or less or 0.12 mass% or less. When the Ca content is in such a range, a higher low-temperature HR discharge performance after charge / discharge cycling can be obtained. The Ca content is, for example, 0.01 mass% or more, and may be 0.03 mass% or more or 0.04 mass% or more.

[0099] The Ca content in the positive electrode current collector may be 0.01 mass% or more (or 0.03 mass% or more) and 0.2 mass% or less, 0.01 mass% or more (or 0.03 mass% or more) and 0.14 mass% or less, 0.01 mass% or more (or 0.03 mass% or more) and 0.12 mass% or less, 0.04 mass% or more and 0.2 mass% or less (or 0.14 mass% or less), or 0.04 mass% or more and 0.12 mass% or less.

[0100] The Sn content in the positive electrode current collector is 0.5 mass% or more. If the Sn content is less than 0.5 mass%, intergranular corrosion is likely to progress, and the low-temperature HR discharge performance after cycling is significantly reduced. From the viewpoint of ensuring a higher corrosion inhibition effect of the positive electrode current collector, the Sn content is preferably 0.8 mass% or more or 1.0 mass% or more. The Sn content is, for example, 5 mass% or less, and may be 3 mass% or less.

[0101] The Sn content in the positive electrode current collector may be 0.5% by mass or more and 5% by mass or less (or 3% by mass or less), 0.8% by mass or more and 5% by mass or less (or 3% by mass or less), or 1.0% by mass or more and 5% by mass or less (or 3% by mass or less).

[0102] The quantitative analysis of Ca and Sn contained in the positive electrode current collector can be performed, for example, in accordance with the lead separation inductively coupled plasma optical emission spectroscopy described in JIS H2105. When analyzing the content of elements contained in the positive electrode current collector of the positive electrode plate removed from a lead-acid battery, first vibrate the positive electrode plate to cause the positive electrode material to fall off from the positive electrode current collector, then use a ceramic knife to remove the positive electrode material remaining around the positive electrode current collector, and collect a part of the part with metallic luster as a sample. The collected sample is decomposed with tartaric acid and dilute nitric acid to obtain an aqueous solution. Hydrochloric acid is added to the aqueous solution to precipitate lead chloride, and the solution is filtered to collect the filtrate. The Ca concentration and Sn concentration in the filtrate are analyzed by a calibration curve method using an inductively coupled plasma (ICP) optical emission spectrometer (e.g., ICPS-8000 manufactured by Shimadzu Corporation), and converted into the Ca content and Sn content per mass of the positive electrode current collector.

[0103] The positive electrode current collector may have a surface layer. The surface layer and the inner layer of the positive electrode current collector may have different compositions. The surface layer may be formed on a part of the positive electrode current collector. The surface layer may be formed only on the grid portion, the edge portion, or the frame portion of the positive electrode current collector.

[0104] The positive electrode material contained in the positive electrode plate contains a positive electrode active material (lead dioxide or lead sulfate) that develops capacity through an oxidation-reduction reaction. The positive electrode material may contain other additives as necessary.

[0105] An unformed paste-type positive electrode plate is obtained by filling a positive electrode current collector with a positive electrode paste, aging it, and drying it. The positive electrode paste is prepared by kneading lead powder, an additive, water, and sulfuric acid.

[0106] A positive plate is obtained by chemically forming an unformed positive plate. Chemical formation can be performed by immersing an electrode plate group including an unformed positive plate in an electrolyte containing sulfuric acid in a battery container of a lead-acid battery and charging the electrode plate group. However, chemical formation may be performed before assembling the lead-acid battery or the electrode plate group.

[0107] (Separator) A separator can be disposed between the negative electrode plate and the positive electrode plate. For example, at least one selected from a nonwoven fabric and a microporous membrane is used as the separator. The thickness of the separator interposed between the negative electrode plate and the positive electrode plate may be selected according to the inter-electrode distance. The number of separators may be selected according to the number of inter-electrode spaces.

[0108] A nonwoven fabric is a mat in which fibers are intertwined without being woven, and is mainly composed of fibers. For example, 60% or more by mass of the nonwoven fabric is made of fibers. As the fibers, glass fibers, polymer fibers (polyolefin fibers, acrylic fibers, polyester fibers (polyethylene terephthalate fibers, etc.), pulp fibers, etc.) can be used. Among them, glass fibers are preferable. The nonwoven fabric may contain components other than fibers (for example, acid-resistant inorganic powder, polymers as binders).

[0109] On the other hand, a microporous membrane is a porous sheet mainly composed of components other than fiber components, and can be obtained, for example, by extruding a composition containing a pore-forming agent (such as at least one of a polymer powder and an oil) into a sheet, and then removing the pore-forming agent to form pores. The microporous membrane is preferably made of an acid-resistant material, and is preferably made mainly of a polymer component. The polymer component is preferably polyolefin (such as polyethylene or polypropylene).

[0110] The separator may be, for example, composed of only a nonwoven fabric or only a microporous membrane. Furthermore, the separator may be, as necessary, a laminate of a nonwoven fabric and a microporous membrane, a laminate of different or the same materials, or a laminate of different or the same materials with recesses and projections interlocked.

[0111] The separator may be in a sheet shape or may be formed in a bag shape. A sheet-shaped separator may be sandwiched between the positive electrode plate and the negative electrode plate. Also, the electrode plate may be sandwiched between a folded sheet-shaped separator. In this case, the positive electrode plate sandwiched between the folded sheet-shaped separator and the negative electrode plate sandwiched between the folded sheet-shaped separator may be stacked, or one of the positive electrode plate and the negative electrode plate may be sandwiched between the folded sheet-shaped separator and stacked with the other electrode plate. Also, the sheet-shaped separator may be folded into a bellows shape, and the positive electrode plate and the negative electrode plate may be sandwiched between the bellows-shaped separator so that the separator is interposed between them. When a separator folded like an accordion is used, the separator may be arranged so that the folded portion is along the horizontal direction of the lead-acid battery (for example, so that the folded portion is parallel to the horizontal direction) or along the vertical direction (for example, so that the folded portion is parallel to the vertical direction). In a separator folded like an accordion, recesses are formed alternately on both main surfaces of the separator. Since a lug is usually formed on the top of each of the positive and negative plates, when the separator is arranged so that the folded portion is along the horizontal direction of the lead-acid battery, the positive and negative plates are arranged only in the recesses on one main surface of the separator (that is, a double separator is interposed between the adjacent positive and negative plates). When the separator is arranged so that the folded portion is aligned with the vertical direction of the lead-acid battery, the positive electrode plate can be accommodated in the recess on one main surface side, and the negative electrode plate can be accommodated in the recess on the other main surface side (that is, a single layer of separator can be interposed between adjacent positive and negative electrode plates.) When a pouch-shaped separator is used, the pouch-shaped separator may accommodate either the positive or negative electrode plate.

[0112] In this specification, the up-down direction of the electrode plate is defined by assuming that the side on which the lugs are provided is the upper side and the opposite side to the lugs is the lower side. The up-down direction of the electrode plate may be the same as or different from the up-down direction of the lead-acid battery in the vertical direction. In other words, the lead-acid battery may be placed either vertically or horizontally.

[0113] (electrolyte) The electrolyte is an aqueous solution containing sulfuric acid, and may be gelled as necessary. The electrolyte may contain at least one selected from the group consisting of cations (e.g., metal cations) and anions (e.g., anions other than sulfate anions (e.g., phosphate ions)) as necessary. Examples of metal cations include at least one selected from the group consisting of sodium ions, lithium ions, magnesium ions, and aluminum ions.

[0114] The specific gravity of the electrolyte in a fully charged lead-acid battery at 20° C. is, for example, 1.20 or more, and may be 1.25 or more. The specific gravity of the electrolyte at 20° C. is 1.35 or less, and preferably 1.32 or less.

[0115] The specific gravity of the electrolyte in a fully charged lead-acid battery at 20° C. may be 1.20 or more and 1.35 or less, 1.20 or more and 1.32 or less, 1.25 or more and 1.35 or less, or 1.25 or more and 1.32 or less.

[0116] The lead-acid battery can be obtained by a manufacturing method including a step of assembling the lead-acid battery by housing a positive electrode plate, a negative electrode plate, and an electrolyte in a battery case. In the step of assembling the lead-acid battery, the separator is usually disposed between the positive electrode plate and the negative electrode plate. The step of assembling the lead-acid battery may include a step of chemically forming at least one of the positive electrode plate and the negative electrode plate, if necessary, after the step of housing the positive electrode plate, the negative electrode plate, and the electrolyte in the battery case. The positive electrode plate, the negative electrode plate, the electrolyte, and the separator are each prepared before being housed in the battery case.

[0117] FIG. 1 shows an external appearance of an example of a lead-acid battery according to one embodiment of the present invention. The lead-acid battery 1 includes a battery case 12 that contains a plate group 11 and an electrolyte (not shown). The battery case 12 is divided into a plurality of cell chambers 14 by partition walls 13. Each cell chamber 14 contains one plate group 11. The opening of the battery case 12 is closed by a lid 15 that has a negative electrode terminal 16 and a positive electrode terminal 17. The lid 15 is provided with a vent plug 18 for each cell chamber. When refilling with water, the vent plug 18 is removed and refilling liquid is added. The vent plug 18 may have a function of discharging gas generated in the cell chamber 14 to the outside of the battery.

[0118] Each electrode plate group 11 is formed by stacking a plurality of negative electrode plates 2 and positive electrode plates 3 with a separator 4 interposed therebetween. Here, a pouch-shaped separator 4 that accommodates the negative electrode plates 2 is shown, but the shape of the separator is not particularly limited. In a cell chamber 14 located at one end of the battery case 12, a negative electrode shelf portion 6 that connects a plurality of negative electrode plates 2 in parallel is connected to a through connector 8, and a positive electrode shelf portion 5 that connects a plurality of positive electrode plates 3 in parallel is connected to a positive electrode column 7. The positive electrode column 7 is connected to a positive electrode terminal 17 outside the lid 15. In a cell chamber 14 located at the other end of the battery case 12, a negative electrode column 9 is connected to the negative electrode shelf portion 6, and a through connector 8 is connected to the positive electrode shelf portion 5. The negative electrode column 9 is connected to a negative electrode terminal 16 outside the lid 15. Each through connector 8 passes through a through hole provided in the partition wall 13 to connect the electrode plate groups 11 of adjacent cell chambers 14 in series.

[0119] The positive electrode shelf 5 is formed by welding the lugs provided on the upper part of each positive electrode plate 3 together by a cast-on-strap method or a burning method. The negative electrode shelf 6 is also formed by welding the lugs provided on the upper part of each negative electrode plate 2 together in the same manner as the positive electrode shelf 5.

[0120] The lid 15 of the lead-acid battery has a single structure (single lid), but is not limited to the illustrated example. The lid 15 may have a double structure including, for example, an inner lid and an outer lid (or a top lid). The lid having a double structure may have a reflux structure between the inner lid and the outer lid for returning the electrolyte to the inside of the battery (inside the inner lid) from a reflux port provided in the inner lid.

[0121] A lead-acid battery according to one aspect of the present invention will be described below.

[0122] (1) A battery comprising a positive electrode plate, a negative electrode plate, and an electrolyte; The positive electrode plate includes a positive electrode current collector and a positive electrode material, The negative electrode plate includes a negative electrode current collector and a negative electrode material, The positive electrode current collector includes a lead alloy containing Ca and Sn, The Ca content in the positive electrode current collector is 0.2 mass% or less, and the Sn content is 0.5 mass% or more, The negative electrode material comprises a first organic shrinkage preventer (excluding a lignin compound) including at least one selected from the group consisting of a monocyclic aromatic compound unit and a bisphenol S compound unit.

[0123] (2) In the above (1), the Ca content in the positive electrode current collector may be 0.14% by mass or less, or 0.12% by mass or less.

[0124] (3) In the above (1) or (2), the Ca content in the positive electrode current collector may be 0.01% by mass or more, 0.03% by mass or more, or 0.04% by mass or more.

[0125] (4) In any one of the above (1) to (3), the positive electrode current collector may have an Sn content of 0.8 mass % or more, or 1.0 mass % or more.

[0126] (5) In any one of the above (1) to (4), the positive electrode current collector may have an Sn content of 5 mass % or less, or 3 mass % or less.

[0127] (6) In any one of the above (1) to (5), the negative electrode material may further contain barium sulfate.

[0128] (7) In the above (6), the content of the barium sulfate in the negative electrode material may be 0.05 mass % or more, 0.1 mass % or more, 0.5 mass % or more, 0.6 mass % or more, or 0.8 mass % or more.

[0129] (8) In the above (6) or (7), the content of the barium sulfate in the negative electrode material may be 5% by mass or less, or 3% by mass or less.

[0130] (9) In any one of the above (1) to (8), the first organic shrink-preventing agent may contain a unit (first unit) of the monocyclic aromatic compound and a unit (second unit) of another aromatic compound.

[0131] (10) In the above (9), the second unit may include at least a bisarene compound unit, and the bisarene compound unit may be at least one selected from the group consisting of a bisphenol S compound unit and a bisphenol A compound unit.

[0132] (11) In the above (10), the bisarene compound unit may include at least a bisphenol S compound unit.

[0133] (12) In any one of the above (1) to (11), the monocyclic aromatic compound unit may include at least a phenolsulfonic acid unit.

[0134] (13) In any one of the above (11) to (13), the molar ratio of the first units to the total amount of the first units and the second units may be 10 mol % or more, 20 mol % or more, 40 mol % or more, or 50 mol % or more.

[0135] (14) In any one of the above (11) to (13), the molar ratio of the first units to the total amount of the first units and the second units may be 90 mol % or less, or 80 mol % or less.

[0136] (15) In any one of the above (1) to (8), the first organic shrink-preventing agent may contain a unit of the bisphenol S compound and a unit of a bisphenol A compound.

[0137] (16) In the above (15), the molar ratio of the bisphenol S compound units to the total amount of the bisphenol S compound units and the bisphenol A compound units in the first organic shrinkage inhibitor may be 40 mol % or more.

[0138] (17) In the above (15) or (16), the molar ratio of the bisphenol S compound units to the total amount of the bisphenol S compound units and the bisphenol A compound units may be 10 mol % or more, 20 mol % or more, 40 mol % or more, or 50 mol % or more.

[0139] (18) In any one of the above (15) to (17), the molar ratio of the bisphenol S compound units to the total amount of the bisphenol S compound units and the bisphenol A compound units may be 90 mol % or less, or 80 mol % or less.

[0140] (19) In any one of the above (1) to (18), the first organic shrink-proofing agent may have a sulfur element content of 300 μmol / g or more, 2000 μmol / g or more, or 3000 μmol / g or more.

[0141] (20) In any one of the above (1) to (19), the sulfur element content of the first organic shrink-proofing agent may be 8000 μmol / g or less, or 7000 μmol / g or less.

[0142] (21) In any one of the above (1) to (18), the first organic shrink-proofing agent may have a sulfur element content of less than 2000 μmol / g.

[0143] (22) In the above (21), the first organic shrink-proofing agent may have a sulfur element content of 300 μmol / g or more.

[0144] (23) In any one of the above (1) to (22), the organic shrink-preventing agent may have a weight average molecular weight (Mw) of 7,000 or more.

[0145] (24) In any one of the above (1) to (23), the weight average molecular weight (Mw) of the organic shrink-preventing agent may be 100,000 or less, or 20,000 or less.

[0146] (25) In any one of the above (1) to (24), the content of the organic shrink-proofing agent contained in the negative electrode material (the total content of the first organic shrink-proofing agent and an organic shrink-proofing agent other than the first organic shrink-proofing agent (second organic shrink-proofing agent)) may be 0.01 mass % or more, or 0.05 mass % or more.

[0147] (26) In any one of the above (1) to (25), the content of the organic shrink-proofing agent contained in the negative electrode material (the total content of the first organic shrink-proofing agent and an organic shrink-proofing agent other than the first organic shrink-proofing agent (second organic shrink-proofing agent)) may be 1.0 mass % or less, or 0.5 mass % or less.

[0148] (27) In any one of the above (1) to (26), the negative electrode material may further contain a carbonaceous material.

[0149] (28) In the above (27), the content of the carbonaceous material in the negative electrode material may be 0.05 mass % or more, or 0.10 mass % or more.

[0150] (29) In the above (27) or (28), the content of the carbonaceous material in the negative electrode material may be 5% by mass or less, or 3% by mass or less.

[0151] (30) In any one of the above (1) to (29), the specific gravity of the electrolyte in the lead-acid battery in a fully charged state at 20° C. may be 1.20 or more, or 1.25 or more.

[0152] (31) In any one of the above (1) to (30), the specific gravity of the electrolyte in the lead-acid battery in a fully charged state at 20° C. may be 1.35 or less, or 1.32 or less.

[0153] [Example] The present invention will be specifically described below based on examples and comparative examples, but the present invention is not limited to the following examples.

[0154] Lead-acid batteries A1-1 to A3-12, R1-1 to R3-2, and B1-1 to B2 (1) Preparation of lead-acid battery (a) Preparation of the negative electrode plate Lead powder, water, dilute sulfuric acid, carbon black, an organic shrinkage inhibitor, and optionally barium sulfate are mixed to obtain a negative electrode paste. At this time, the components are mixed so that the content of the organic shrinkage inhibitor in the negative electrode material, which is determined by the procedure described above, and the content of the carbon black are 0.10 mass% and 0.30 mass%, respectively. Barium sulfate is mixed with other components so that the content of barium sulfate, which is determined by the procedure described above, is the value shown in Table 1. The negative electrode paste is filled into the mesh portion of an expanded lattice made of a Pb-Ca-Sn alloy as a negative electrode current collector, and the mixture is aged and dried to obtain an unformed negative electrode plate.

[0155] As the organic shrinkage inhibitor, the condensation products shown in Table 1 are used. The condensation products shown in Table 1 are as follows. The molar ratio of the monomers in each organic shrinkage inhibitor corresponds to the molar ratio of the units determined by the above-mentioned procedure. a1: Formaldehyde condensate of bisphenol S and phenolsulfonic acid (=2:8 (molar ratio)) (sulfur element content: 4000 μmol / g, Mw: 8000) a2: Formaldehyde condensate of bisphenol A and phenolsulfonic acid (=2:8 (molar ratio)) (sulfur element content: 4000 μmol / g, Mw: 8000) a3: Condensate of bisphenol S, bisphenol A (=4:6 (molar ratio)) and formaldehyde in the presence of sodium sulfite (sulfur element content: 5000 μmol / g, Mw: 9000) b1: Sodium lignosulfonate (sulfur element content: 600 μmol / g, Mw: 5500) b2: Condensation product of bisphenol A and formaldehyde in the presence of sodium sulfite (sulfur element content: 3000 μmol / g, Mw: 9000)

[0156] (b) Preparation of the positive electrode plate The raw lead powder is mixed with an aqueous sulfuric acid solution to obtain a positive electrode paste. The positive electrode paste is filled into the mesh of a lead alloy grid as a positive electrode current collector, and the grid is aged and dried to obtain an unformed positive electrode plate. The positive electrode current collector is an expanded grid made of a Pb-Ca-Sn alloy with the Ca content and Sn content shown in Table 1, as determined by the above-mentioned procedure.

[0157] (c) Preparation of lead-acid battery The unformed negative electrode plates are housed in a pouch-shaped separator formed of a microporous polyethylene film, and five unformed negative electrode plates and four unformed positive electrode plates form an electrode plate group. The plate group is inserted into a battery case, electrolyte is poured in, and chemical formation is performed in the battery case to produce flooded lead-acid batteries E1 to E3 and R1 to R5 with a rated voltage of 12V and a rated capacity of 30Ah (5-hour rate). The electrolyte used is a sulfuric acid aqueous solution with a specific gravity of 1.28 (20°C) after chemical formation. The above chemical formation brings the lead-acid battery into a fully charged state.

[0158] (2) Evaluation (2-1) Initial performance (a) Low temperature HR discharge performance The prepared lead-acid battery is discharged at a discharge current of 150A at -15°C±0.3°C until the terminal voltage reaches 1V / cell, and the discharge time (discharge duration) (s) at this time is calculated. The ratio (%) of the discharge duration of lead-acid battery B1-3 set at 100 is used as an index of low-temperature HR discharge performance.

[0159] (b) Charge acceptance The produced lead-acid battery is used to measure the amount of electricity at 10 seconds. Specifically, the lead-acid battery is discharged at 7.2A for 30 minutes. Next, the lead-acid battery is charged at a constant current and constant voltage of 2.4V / cell with the upper limit of the current being 100A, and the accumulated amount of electricity for 10 seconds (the amount of electricity at 10 seconds) is measured. Both operations are carried out in a water tank at 25°C±0.3°C.

[0160] (2-2) Low-temperature HR discharge performance after charge-discharge cycles The prepared lead-acid battery is discharged at 25A for 4 minutes. Then, the lead-acid battery is charged at 2.47V / cell for 10 minutes with the upper limit of the current being 25A. This discharge and charge cycle is counted as one cycle, and is repeated 960 times. Both operations are performed in a water tank at 60℃±0.5℃.

[0161] After repeating the above discharge and charge cycles, the discharge duration is calculated using the procedure in (2-1)(a) above. The ratio (%) of the discharge duration of the lead-acid battery B1-2, set at 100, is used as an index of low-temperature HR discharge performance. The results are shown in Table 1.

[0162] [Table 1]

[0163] As shown in Table 1, the lead-acid battery using the first organic shrinkage inhibitors a1 to a3 has a significantly improved low-temperature HR discharge performance after charge-discharge cycles compared to the lead-acid battery using sodium ligninsulfonate or a condensate of bisphenol A. In the lead-acid battery using sodium ligninsulfonate, the change in low-temperature HR discharge performance after charge-discharge cycles is 4% or less even if the Ca content, Sn content, or barium sulfate content in the positive electrode current collector is changed. In contrast, the lead-acid battery using the first organic shrinkage inhibitor has a significantly improved low-temperature HR discharge performance after charge-discharge cycles of 8% to 50%.

[0164] In addition, the low-temperature HR discharge performance after cycling is significantly improved when the Ca content in the positive electrode current collector is 0.2 mass% or less, compared to when it exceeds 0.2 mass%. Similarly, the low-temperature HR discharge performance after cycling is significantly improved when the Sn content in the positive electrode current collector is 0.5 mass% or more, compared to when it is less than 0.5 mass%. Moreover, such an improvement effect cannot be obtained when sodium lignosulfonate is used, and it can be said to be an effect specific to the first organic shrink-proofing agent.

[0165] When sodium lignin sulfonate is used, the charge acceptance and low-temperature HR discharge performance after charge-discharge cycles are almost unchanged even when the barium sulfate content increases from 0.6% by mass to 0.8% by mass. However, when the first organic shrinkage inhibitor is used, the charge acceptance and low-temperature HR discharge performance after charge-discharge cycles are significantly increased when the barium sulfate content increases from 0.6% by mass to 0.8% by mass. Therefore, from the viewpoint of ensuring even higher charge acceptance and low-temperature HR discharge performance after charge-discharge cycles, the barium sulfate content is preferably 0.8% by mass or more. [Industrial Applicability]

[0166] The negative electrode plate and the lead-acid battery according to one aspect of the present invention are applicable to valve-regulated and liquid-type lead-acid batteries. The lead-acid battery can be suitably used, for example, as a power source for starting automobiles or motorcycles, a natural energy storage device, and a power source for industrial storage devices such as electric vehicles (forklifts, etc.). Note that these uses are merely examples and are not limited to these uses. [Explanation of symbols]

[0167] 1:Lead acid battery 2: Negative plate 3: Positive plate 4: Separator 5: Positive electrode shelf 6: Negative electrode shelf 7: Positive pole 8: Through connector 9: Negative pole 11: Plate group 12:Battery container 13: Bulkhead 14: Cell Room 15: Lid 16: Negative terminal 17: Positive terminal 18: Liquid outlet plug

Claims

1. The battery includes a positive electrode plate, a negative electrode plate, and an electrolyte solution. The positive electrode plate includes a positive electrode current collector and a positive electrode material, The negative electrode plate includes a negative electrode current collector and a negative electrode material, The positive electrode current collector includes a lead alloy containing Ca and Sn, The Ca content in the positive electrode current collector is 0.2 mass% or less, and the Sn content is 0.5 mass% or more, The negative electrode material includes a first organic shrink-proofing agent excluding a lignin compound, The first organic shrink-proofing agent includes a first unit which is a unit of a monocyclic aromatic compound and a second unit which is a unit of another aromatic compound, the first unit includes at least a phenolsulfonic acid unit, The second unit comprises a unit of a bisarene compound.

2. 10. The lead-acid battery of claim 1, wherein the negative electrode material further comprises barium sulfate.

3. The lead-acid battery according to claim 2 , wherein the content of the barium sulfate in the negative electrode material is 0.6 mass % or more.

4. A lead-acid battery described in any one of claims 1 to 3, wherein the bisarene compound unit is at least one type selected from the group consisting of a bisphenol S compound unit and a bisphenol A compound unit.

5. 5. The lead acid battery according to claim 4, wherein the unit of the bisarene compound is at least a unit of the bisphenol S compound.

6. The lead acid battery according to any one of claims 1 to 5, wherein a molar ratio of the first units to a total amount of the first units and the second units is 10 mol% or more and 90 mol% or less.

7. The lead-acid battery according to any one of claims 1 to 6, wherein the sulfur element content of the first organic shrinkage regulator is 300 µmol / g or more and 8000 µmol / g or less.

8. The lead acid battery according to any one of claims 1 to 7, wherein the weight average molecular weight (Mw) of the first organic shrinkage inhibitor is 7000 or more and 20,000 or less.

Citation Information

Patent Citations

  • Lead-acid battery

    JP2002134114A

  • Manufacturing method of lead-acid battery

    JP2004071477A

  • Liquid type lead acid battery

    JP2013161606A

  • Lead storage battery

    JP2017079166A

  • Phenolic resin, electrode, lead-acid battery, methods for producing them, and resin composition

    JP2017155111A